Pengaruh Konsumsi Dark Chocolate terhadap Kecemasan pada Ibu Post Sectio Caesarea - Laily Wahidatul Oktavia; Maria Ulfa (Journal of Ners and Midwifery, 2016)
The consumption of dark chocolate on the second day of mother post section caesarea can reduce anxiety, since the asetosal substance can stimulate the limbic system of hypothalamus to suppress the anxiety. Method: The research design was a Quasy experimental. The research sample was 8 mother post sectio caesarea in Ngudi Waluyo Hospital Cempaka Wlingi at August 14th, up to September 14th, 2015, it was chosen using accidental sampling. The data analyzed by Wilcoxon rank test. Result: showed a decrease in the percentage of anxiety scale before and after eating dark chocolate in which the anxiety scale of 87.5% to 20%. Based on statistical analysis showed Wlicoxon Signed Rank Test p value = 0,008, so p value = 0.008 <ï¡ = 0.05. Discussion: relaxed condition was needed in the process of recovery condition after partum mothers, especially post surgery. Psychological factors like family support also needed to optimize all of the action taken.